Orkes Puisi Sampak Gusuran : the Creativity of Processing and Symbolic Meanings in Action of Art for the Art Consumer Community - Amaliani, Mina; Wadiyo, Wadiyo; Rohidi, Tjetjep Rohendi (Universitas Negeri Semarang, 2018)
This research raises the problem about an art group located in Pati Central Java named Orkes Puisi Sampak Gusuran. The group has created the art of musical poetry. The purpose of this study was to obtain a picture of the form of creativity and symbolic meaning of the work of the Orkes Puisi Sampak Gusuran for the society of art consumer. This research used qualitative method and used an interdisciplinary approach to find out the symbolic meaning, using symbolic interaction theory. The data collection techniques used are interviews, observation, and document studies. The results of this study indicate that; 1)there are poetry reading techniques must be maintained in order to maintain the meaning of the deepest meaning of a poetry to be away from melodic readings such as language in a songs, although the music as a companion is still presented as a builder of nuance 2)the syllable of poetry can be widened or narrow to adjust to music without reducing the essence of his poetry. From the mixing of instruments, musical genres and mixed arrangements, a new musical arrangement is created that is sometimes undetectable in its genre. This is where the originality the work of Orkes Puisi Sampak Gusuran, where the arrangement sounded flowing, following the atmosphere of poetry, strengthen it into music that is different from others but still strong as a music or as a poetry. Meanwhile the symbolic meaning that can be concluded is: 1)works of poetry Orkes Puisi Sampak Gusuran symbolize life that occurred in society and also a relation to God 2)the use of traditional instruments is a relationship with the ancestors who remain woven in the present.